THE EFFECTS OF WORK DISCIPLINE AND COMPENSATION TOWARDS PERFORMANCE OF EMPLOYEES BOARD STAFFING AND HUMAN RESOURCES DEVELOPMENT (BKPSDM) OF KABUPATEN KARAWANG, WEST JAVA - Asyhadi, Farhan; Isyanto, Puji; R. , Adjeng Mariana (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the condition of Work Discipline, Compensation and Employee Performance Award, as well as to know how big the influence of variable Work Discipline and Compensation for Employee Performance Human Resources Agency and Human Resources Development, either partially or simultaneously. In this study, the authors expect this journal into benefits and can provide information and knowledge sumbangsi theoretically and practically. This research was conducted with descriptive methods are: collecting, presenting, analyzing and testing hypotheses, and make inferences and suggestions. In this research, the researcher found that work discipline and compensation have a positive significant impact towards performance of employees of BKPSDM Kabupaten Karawang.